2015
DOI: 10.3390/jcm4030460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Markers in Acute Myeloid Leukemia

Abstract: Genetics play an increasingly important role in the risk stratification and management of acute myeloid leukemia (AML) patients. Traditionally, AML classification and risk stratification relied on cytogenetic studies; however, molecular detection of gene mutations is playing an increasingly important role in classification, risk stratification, and management of AML. Molecular testing does not take the place of cytogenetic testing results, but plays a complementary role to help refine prognosis, especially wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 81 publications
(185 reference statements)
2
53
0
3
Order By: Relevance
“…In previous studies a favourable outcome for the CEBPA mutation has been reported. CEBPA mutations improve the prognosis of AML with normal cytogenetics from intermediate to favorable (Yohe, 2015). Present study also reveals a significant favorable impact for the mutated patients with respect to wild type in overall cases (P=0.028).…”
Section: Discussionsupporting
confidence: 57%
“…In previous studies a favourable outcome for the CEBPA mutation has been reported. CEBPA mutations improve the prognosis of AML with normal cytogenetics from intermediate to favorable (Yohe, 2015). Present study also reveals a significant favorable impact for the mutated patients with respect to wild type in overall cases (P=0.028).…”
Section: Discussionsupporting
confidence: 57%
“…33 Notably, MP-A08 is known to be equally effective at inhibiting human and mouse sphingosine kinases. 33 This therapeutic response occurred in 2 independent AML samples, both with normal karyotype, carrying the FLT3-ITD mutation and either IDH1 or IDH2 mutations, a common occurrence in AML, 54 suggesting SPHK1-directed therapies may have utility across this spectrum of AML. Notably, cells from patient AML8, harboring the 11q23 MLL translocation, were nonresponsive to MP-A08 in vivo, consistent with our subsequent findings that SPHK1 inhibition in these cells did not result in loss of MCL1, a protein known to be critical for AML cell survival.…”
Section: Org Frommentioning
confidence: 99%
“…Several types of leukemia have been identified, including acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), chronic lymphoblastic leukemia (CLL) and chronic myeloid leukemia (CML). The existence of LSCs was first described in AML [119] and many studies have identified mutations in different genes [reviewed in [120], and many other genes have been described in CML [121]. The existence of LSCs derived by malignant transformation of stem cells for is less clear for ALL, and instead it appears to be caused by a variety of mutated committed progenitors [122].…”
Section: Stem Cell Behavior In Different Diseasesmentioning
confidence: 99%